A remarkable new species of Geastrum with an elongated branched stipe - Cabral, Tiara Sousa; Sousa, Julieth de Oliveira; Silva, Bianca Denise Barbosa da; Martín, María Paz; Clement, Charles Roland; Baseia, Iuri Goulart (Mycoscience, 2017)
Based on morphological and molecular analysis, we describe the new species Geastrum verrucoramulosum, discriminated from other species in the section Exareolata mainly by an elongated, verrucose, branched stipe. This new species is currently known from two forest locations in central and southwestern Amazonia. Species description, images, and taxonomic discussion of both morphological and molecular data are provided. © 2017 The Mycological Society of Japan